The Role of the Study of Science for the 2022-2023 Period in Arabic Learning for Islamic Boarding School Students in Lamongan Regency - Iza Mufidah; Khizanatul Hikmah (Universitas Muhammadiyah Sidoarjo, 2022)
This article aims to determine the role of the study of science in learning Arabic as well as the supporting and inhibiting factors in learning Arabic at the Al-Mizan Muhammadiyah Lamongan Islamic Boarding School for the period 2022-2023. The approach that the researcher uses is a qualitative descriptive approach using data collection techniques through observation, interviews and documentation. The results showed that there were ilqo 'activities held every Monday and Thursday, as well as muhadatsah activities which were held every Sunday morning. There are several factors that will support and hinder Arabic learning, namely: 1) The existence of rules and obligations as female students in participating in activities. 2) holding muhadatsah every Sunday morning and ilqo 'every Monday and Thursday as an addition to the daily mufrodat. 3) There is a special program or language class focused on language learning enthusiasts. The inhibiting factors are: 1) The lack of mufrodat that has not been mastered and taught. 2) Lack of awareness and interest of female students in learning Arabic. 3) Lack of ability of the PIP section who is a teacher and mentor in learning Arabic.